Identification of Volatile Compounds of Oil Palm Flower (Elaeis guineensis Jacq.) with Gas Chromatography and Mass Spectrometry Based on the Difference in Time - Sudarjat Sudarjat; Ichsan Nurul Bari; Unang Supratman; Fizrul Indra Lubis (Universitas Gadjah Mada, 2023)
The pollination process in oil palm is assisted by the insect Elaeidobius kamerunicus, which occurs when male and female flowers bloom producing volatile compounds that act as attractants. This study aims to identify volatile compounds in oil palm flowers based on differences in times with gas chromatography mass spectrometry (GC-MS). The research steps include determining the time of the release of volatile compounds in oil palm flowers, extracted using steam distillation, and identification by GC-MS. There are different times of the release of volatile compounds for each type of oil palm flower. Three times by male flowers, at 08:00 am, 11:00 am and 14:00 pm, with the highest volatile compounds at 14:00 pm. Meanwhile, female flowers occurred at 09:00 am, 12:00 am and 15:00 pm, with the highest volatile compounds at 12:00 am. The results of the GC-MS analysis showed that 21 and 19 volatile compounds were identified, with a total of 38 different types. Estragole compounds were dominant in both types of flowers and did not show significant differences in the area sum values at each time of observation. These results indicated the importance of estragole compound for the pollination process in oil palm.